A Comparative Study of Big Data Marketing and Traditional Marketing in the Age of Internet. (June 2020) - Han, Xiaoxiao
Abstract: The Internet age is constantly developing and being perfected, and the marketing strategy of the big data of the industrial and commercial enterprises in the Internet age is also constantly developing and flourishing. We can think of Internet applications as providing businesses with the possibility of real-time marketing strategy development. This paper introduces the Data Collection Strategy and enterprise marketing strategy. Facing the traditional marketing method, the new marketing method difference and the novel characteristic are excavated gradually. In today's marketing methods are very complex times, if the industrial and commercial enterprises do not forge ahead, it will be eliminated by the Times.